Implementation of Interactive Tourist Information Media with The Theme of “Sparkling Surabaya” - Raharja, Crisientia Pranata; Saputra, Hoo Leony Gracia Budi (Prasetiya Mulya Publishing, 2019)
Surabaya, the city of heroes, was a silent witness of Arek Suroboyo’s struggle against the colonial invaders. As a result, it made a huge impact on the birth of many historical relics and triggered Surabaya to develop their tourism potential. Through “Sparkling Surabaya” branding, facilities that were provided by the government are very diverse, but public awareness of the tourism potential was still lacking. This had become the government's concern to introduce Surabaya with a new face by presenting something that can attract citizens of Surabaya that was very fluent in technologies. This research aims to create interactive media that can attract citizen of Surabaya to become more aware of the tourism potential. The method applied to solve this problem is design thinking, which is understand, ideate, prototyping, and test. The result of this research is the design of an tourist information interative media, by creating an open passageway that was placed in strategic locations such as malls, parks, and sidewalk access to public transportation. The usage of technology could support Surabaya tourism with interactive methods and made an impact on improving the economy of Surabaya.